Activated carbon loaded zinc manganate photocatalytic renewable adsorbent as well as preparation method and application thereof
Through the preparation of photocatalytic renewable adsorbents supported by activated carbon, the problem of removing tannin acid in zinc smelting is solved, and efficient adsorption and photocatalytic degradation are achieved, with good recycling and environmental protection advantages.
Patent Information
- Application Number
- CN202411396349.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-08
AI Technical Summary
The prior art is difficult to effectively remove tannin acid in zinc leaching during zinc smelting, resulting in an increase in the viscosity of the electrolyte, a decrease in the electric efficiency, and may cause secondary pollution.
The photocatalytic renewable adsorbent is prepared by co-precipitation-calcination and mechanical grinding, and combined with acid or alkali activated activated activated carbon to form a photocatalyst with a porous structure and a large specific surface area.
It realizes efficient adsorption and photocatalytic degradation of tannin acid, has good adsorption photocatalytic regeneration ability and recycling, avoids secondary pollution, and improves the treatment efficiency of zinc leaching liquid.
Smart Images

Figure CN119386854A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to an activated carbon-supported zinc manganate (AC / ZnMn2O4) photocatalytic regenerable adsorbent and a preparation method and application thereof. Background Art
[0002] In the hydrometallurgical zinc smelting process, germanium is a rare associated metal with high recovery value, which is enriched in zinc oxide dust. At present, adding excess tannic acid to the acid leaching solution of zinc oxide dust to precipitate germanium is the main means of recovering germanium in the zinc smelting process. However, a large amount of excess tannic acid returns to the leaching solution after liquid-solid separation, which increases the viscosity of the electrolyte and reduces the electrical efficiency. In severe cases, it causes cathode zinc to dissolve back or even burn the plate. The main method for removing tannic acid from zinc leaching solution in industry is activated carbon adsorption. This method can only adsorb a certain amount of tannic acid, and cannot achieve the effect of degrading tannic acid and reusing it. It is even easy to form secondary pollution after use. Photocatalysis, as an ideal green technology to solve energy and environmental problems, has broad application prospects in the efficient degradation of organic matter.
[0003] As a new type of spinel photocatalyst, ZnMn2O4 has the advantages of visible light response, good photochemical stability and excellent catalytic activity. At the same time, ZnMn2O4 has low solubility in acidic environment, and the dissolved zinc and manganese ions will not cause secondary pollution to the zinc leaching solution. However, the adsorption performance and recyclability of ZnMn2O4 still need to be improved. Summary of the invention
[0004] In order to solve the technical problems and deficiencies in the prior art, the object of the present invention is to provide an activated carbon supported zinc manganate (AC / ZnMn2O4) photocatalytic regenerable adsorbent and a preparation method and application thereof.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing an activated carbon supported zinc manganate (AC / ZnMn2O4) photocatalytic regenerable adsorbent, comprising the following steps:
[0007] (1) Preparation of ZnMn2O4:
[0008] Add zinc acetate (CH3COO)2Zn·2H2O and manganese acetate (CH3COO)2Mn·4H2O into ethanol-water solution and stir until completely dissolved to obtain solution A;
[0009] Add oxalic acid H2C2O4·2H2O to ethanol-water solution and stir until completely dissolved to obtain solution B;
[0010] The solution A is quickly poured into the solution B, heated and stirred to obtain a mixed solution, and after the mixed solution is cooled to room temperature, it is filtered, washed and dried to obtain a precursor;
[0011] The precursor is calcined to obtain ZnMn2O4 with a long strip morphology;
[0012] (2) activating the activated carbon AC using an acid solution or an alkaline solution; preferably, activating the activated carbon AC using an alkaline solution;
[0013] (3) Preparation of AC / ZnMn2O4 photocatalytic regenerable adsorbent:
[0014] The ZnMn2O4 obtained in step (1) and the activated carbon AC obtained in step (2) are fully ground in anhydrous ethanol until the ZnMn2O4 and AC are evenly mixed and a viscous paste appears, showing a brown-gray color. After drying, an AC / ZnMn2O4 photocatalytic regenerable adsorbent is obtained.
[0015] Preferably, in step (1), the total metal ion concentration of zinc and manganese in the solution A is 0.02 to 0.16 mol / L.
[0016] Preferably, in step (1), the molar ratio of zinc acetate to manganese acetate is 1:2, and the molar ratio of oxalic acid to zinc acetate is 3-3.6:1.
[0017] Preferably, in step (1), the heating and stirring are performed at a heating temperature of 50 to 60° C., a stirring rate of 500 to 1000 r / min, and a stirring time of 2 to 2.5 h.
[0018] Preferably, in step (1), the volume ratio of ethanol to water in the ethanol-water solution is 9:1.
[0019] Preferably, in step (1), the precursor is heated to 450-550° C. at a heating rate of 2-10° C. / min for calcination, and the calcination holding time is 2-2.5 h.
[0020] The volume ratio of ethanol to water in the precipitation medium plays a key role in the change of the aspect ratio of the ZnMn2O4 particles. By adopting the preferred embodiment of the above step (1), a long strip of porous ZnMn2O4 with a large specific surface area and pore volume can be prepared, which is conducive to the full contact between the photocatalyst and the degradation target, and provides more mass transfer channels and reaction active sites, reduces the recombination rate of photogenerated electrons and holes, and improves the photocatalytic degradation efficiency.
[0021] Preferably, in step (2), the mass-to-liquid ratio of activated carbon to acid / alkaline solution is 1:5-1:4 (g / mL); preferably, the alkaline solution is 1%-5% (w / w) KOH solution, and the acid solution is 4-5 mol / L nitric acid solution.
[0022] The specific operations are as follows:
[0023] Add activated carbon to KOH solution, stir and mix thoroughly at room temperature for a period of time, filter, wash with dilute hydrochloric acid and distilled water continuously to make the pH of activated carbon filtrate neutral, and then dry overnight to obtain alkali-activated AC;
[0024] Alternatively, activated carbon is added to a nitric acid solution, heated and stirred continuously for a period of time, filtered, and continuously washed with distilled water to make the pH of the activated carbon filtrate neutral, and then dried overnight to obtain acid-activated AC.
[0025] The stirring rate is 500-700 r / min, the stirring time is 22-24 h, and the heating temperature during heating and stirring is 70-80° C.
[0026] Preferably, in step (3), the mass ratio of activated carbon AC and ZnMn2O4 is 1:10 to 3:10.
[0027] In a second aspect, the present invention provides an activated carbon supported zinc manganate (AC / ZnMn2O4) photocatalytic regenerable adsorbent, which is composed of activated carbon AC and zinc manganate ZnMn2O4 and is prepared by the aforementioned preparation method, wherein the mass ratio of AC to ZnMn2O4 is 1:10 to 3:10.
[0028] In a third aspect, the present invention provides the use of the aforementioned activated carbon-supported zinc manganate (AC / ZnMn2O4) photocatalytic regenerable adsorbent in the cyclic adsorption of tannic acid.
[0029] Compared with the existing technology, it has the following characteristics:
[0030] (1) The AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared by the present invention adopts a simple coprecipitation-calcination and mechanical grinding method, which has little pollution to the zinc leaching solution, strong operability, and does not generate secondary pollution, and has excellent adsorption performance for tannic acid.
[0031] (2) The AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared by the present invention has a porous structure and a large specific surface area.
[0032] (3) The AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared by the present invention has good adsorption photocatalytic regeneration ability and recycling, and has good practical value and potential application prospects in removing tannic acid in zinc leachate. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 (a) SEM and (be) C, O, Zn, and Mn element distribution diagram of the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1.
[0034] Figure 2 This is the N2 adsorption-desorption curve of the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1.
[0035] Figure 3 This is the pore size distribution diagram of the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1.
[0036] Figure 4 It is a diagram showing the adsorption effect of tannic acid on the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1, Example 2, Comparative Example 1 and the alkali-activated AC prepared in Example 1.
[0037] Figure 5 is a bar graph of the cyclic stability of the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1; Figure 5 1 is the adsorption rate of tannic acid degraded by AC / ZnMn2O4 photocatalytic regenerative adsorbent in the first cycle for 120 minutes; 2 is the adsorption rate of tannic acid degraded by AC / ZnMn2O4 photocatalytic regenerative adsorbent in the second cycle for 120 minutes; 3 is the adsorption rate of tannic acid degraded by AC / ZnMn2O4 photocatalytic regenerative adsorbent in the third cycle for 120 minutes; 4 is the adsorption rate of tannic acid degraded by AC / ZnMn2O4 photocatalytic regenerative adsorbent in the fourth cycle for 120 minutes. DETAILED DESCRIPTION
[0038] The objectives, specific implementation methods and advantages of the present invention are described in detail below, but the present invention is not limited to the following description.
[0039] The present invention compounds AC and ZnMn2O4 to construct an AC / ZnMn2O4 photocatalytic regenerable adsorbent, which is of great significance for enhancing the adsorption performance of AC on tannic acid in zinc leaching solution, realizing the recycling of the adsorbent and avoiding secondary pollution.
[0040] The technical solution of the present invention is described below in conjunction with specific embodiments:
[0041] Embodiment 1:
[0042] (1) Preparation of ZnMn2O4:
[0043] 0.220g zinc acetate (CH3COO)2Zn·2H2O and 0.490g manganese acetate (CH3COO)2Mn·4H2O were added to an ethanol-water solution (90mL+10mL), and the mixture was stirred until completely dissolved to obtain a solution A with a total concentration of zinc and manganese metal ions of 0.02mol / L. Similarly, 0.378g oxalic acid H2C2O4·2H2O was added to an ethanol-water solution (45mL+5mL) and stirred until completely dissolved to obtain a solution B. Solution A was quickly poured into solution B and stirred at 60°C and 1000r / min for 2h to obtain a mixed solution. After the mixed solution was cooled to room temperature, it was filtered, washed and dried to obtain a precursor sample. Finally, the dried precursor was calcined in an air atmosphere, and calcined at 450°C for 2h at a heating rate of 2°C / min to finally obtain a long strip of porous ZnMn2O4.
[0044] (2) Preparation of acid or alkali activated carbon:
[0045] 25g AC was added to 100mL 1% (w / w) KOH solution, stirred continuously for 24h at room temperature, filtered, and continuously washed with dilute hydrochloric acid and distilled water to make the pH of the AC filtrate neutral, and then dried overnight to obtain alkali-activated AC; 20g AC was added to 100mL 5mol / L nitric acid solution, stirred continuously for 24h at 80°C water bath temperature, filtered, continuously washed with distilled water to make the pH of the activated carbon filtrate neutral, and then dried overnight to obtain acid-activated AC.
[0046] (3) Preparation of AC / ZnMn2O4 photocatalytic regenerable adsorbent:
[0047] 0.10 g of ZnMn2O4 obtained in step (1) and 0.01 g of alkali-activated activated carbon obtained in step (2) were placed in an agate mortar, 1 to 2 mL of anhydrous ethanol were added, and the mixture was fully ground with an agate mortar rod for 30 minutes until ZnMn2O4 and AC were evenly mixed and a thick paste appeared, showing a brown-gray color. After drying, an AC / ZnMn2O4 photocatalytic regenerable adsorbent was obtained.
[0048] The field scanning electron microscope photo of the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in this example is detailed in Figure 1 ,Depend on Figure 1 It can be seen that ZnMn2O4 covers the smooth AC surface in the form of thin strips, indicating that ZnMn2O4 and AC are tightly composited together.
[0049] The nitrogen adsorption / desorption curve and pore size distribution of the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in this example are detailed in Figure 2 and Figure 3As can be seen from the figure, AC / ZnMn2O4 photocatalytic regenerable adsorbent has a large specific surface area and pore volume, which are 90.885m 2 ·g -1 and 0.210cm 3 ·g -1 The pore diameter is mainly distributed in the range of 5-120nm, with an average pore diameter of 46nm, which is a porous structure.
[0050] Embodiment 2:
[0051] The difference between this embodiment and embodiment 1 is that the activated carbon in step (3) is acid-activated AC. The other steps are the same as those in embodiment 1.
[0052] Embodiment 3:
[0053] The difference between this embodiment and embodiment 1 is that the total concentration of zinc and manganese metal ions in step (1) is 0.16 mol / L. The other steps are the same as those in embodiment 1.
[0054] Embodiment 4:
[0055] The difference between this embodiment and embodiment 1 is that the heating temperature in step (1) is 50° C. The other steps are the same as those in embodiment 1.
[0056] Embodiment 5:
[0057] The difference between this embodiment and embodiment 1 is that the stirring rate in step (1) is 500 r / min.
[0058] Embodiment 6:
[0059] The difference between this embodiment and embodiment 1 is that the calcination temperature in step (1) is 400°C.
[0060] Embodiment 7:
[0061] The difference between this embodiment and embodiment 1 is that the heating rate in step (1) is 10°C / min.
[0062] Embodiment 8:
[0063] The difference between this embodiment and embodiment 1 is that the amount of activated carbon activated by alkali in step (3) is 0.02 g.
[0064] Embodiment 9:
[0065] The difference between this embodiment and embodiment 1 is that the amount of activated carbon activated by alkali in step (3) is 0.03 g.
[0066] The difference between this embodiment and embodiment 1 is that the activated carbon in step (3) is untreated commercial activated carbon.
[0067] Application examples:
[0068] 1. Adsorption performance experiment
[0069] 20 mg of the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1, Example 2, Example 8, Example 9, Comparative Example 1 and the alkali-activated AC prepared in Example 1 were weighed and added to 50 mL of an aqueous solution with an initial concentration of 200 mg·L -1 tannic acid solution was mixed in a quartz tube, and stirred at a constant stirring rate for 10, 20, 35, 60, 90, and 120 minutes at room temperature in a dark environment. 2 mL of supernatant was taken, and the solution was filtered with a 0.22 μm filter membrane and the absorbance was measured by colorimetric method to obtain the residual concentration of tannic acid and calculate the adsorption rate.
[0070] The adsorption effect of AC / ZnMn2O4 photocatalytic regenerable adsorbent and alkali-activated AC on tannic acid prepared in Example 1, Example 2, Example 8, Example 9 and Comparative Example 1 of the present invention is shown in the figure. Figure 4 Among them, the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1 has the fastest adsorption rate (the adsorption rate of tannic acid within 20 minutes is 71.4%), and the adsorption rate of tannic acid within 120 minutes is the highest, which is 98.3%. The adsorption rates of the remaining samples are shown in Table 1. This shows that the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1 has excellent adsorption performance for tannic acid.
[0071] Table 1 Adsorption rate of tannic acid in each experimental group
[0072]
[0073]
[0074] 2. Cycle performance test
[0075] A photocatalytic reaction was carried out under sunlight simulated by a 500W xenon lamp. The tannic acid solution containing the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1 after the first adsorption was placed under xenon lamp light, and a photocatalytic regeneration experiment was carried out at room temperature. After 150 minutes of illumination, all the AC / ZnMn2O4 photocatalytic regenerable adsorbent adsorbed for the first time was centrifuged and dried to obtain the AC / ZnMn2O4 photocatalytic regenerable adsorbent of the first cycle.
[0076] The AC / ZnMn2O4 photocatalytic regenerable adsorbent obtained in the first cycle of photocatalytic regeneration experiment 1 was added to 50 mL of an initial concentration of 200 mg·L -1The tannic acid solution was dark adsorbed for 120 minutes to obtain a tannic acid solution containing the AC / ZnMn2O4 photocatalytic regenerable adsorbent after the second adsorption. The removal rate was as follows Figure 5 This process was repeated four times to obtain the tannic acid removal rate at each cycle number.
[0077] The cyclic stability bar graph of the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1 of the present invention is shown in Figure 5 There is no obvious attenuation in the removal rate of tannic acid in the four cycles, which proves that the AC / ZnMn2O4 photocatalytic regenerable adsorbent prepared in Example 1 has a stable cyclic removal effect and strong repeated regeneration, which is conducive to actual production application.
[0078] The above examples only express several preferred implementations of the present invention, and the detailed description cannot be understood as limiting the scope of the present invention. Under the premise of not departing from the technical concept and characteristics of the present invention, all modifications and equivalent modifications made according to the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing an activated carbon-supported zinc manganate photocatalytic regenerable adsorbent, characterized in that: The following steps are involved: (1) Preparation of ZnMn2O4: Add zinc acetate (CH3COO)2Zn·2H2O and manganese acetate (CH3COO)2Mn·4H2O into ethanol-water solution and stir until completely dissolved to obtain solution A; Add oxalic acid H2C2O4·2H2O to ethanol-water solution and stir until completely dissolved to obtain solution B; The solution A is quickly poured into the solution B, heated and stirred to obtain a mixed solution, and after the mixed solution is cooled to room temperature, it is filtered, washed and dried to obtain a precursor; The precursor is calcined to obtain ZnMn2O4 with a long strip morphology; (2) Activating activated carbon AC using acid solution or alkaline solution; (3) Preparation of AC / ZnMn2O4 photocatalytic regenerable adsorbent: The ZnMn2O4 obtained in step (1) and the activated carbon AC obtained in step (2) are fully ground in anhydrous ethanol until the ZnMn2O4 and AC are evenly mixed and a viscous paste appears, showing a brown-gray color. After drying, an AC / ZnMn2O4 photocatalytic regenerable adsorbent is obtained.
2. The preparation method according to claim 1, characterized in that: In step (1), the total metal ion concentration in the solution A is 0.02 to 0.16 mol / L.
3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of zinc acetate to manganese acetate is 1:2, and the molar ratio of oxalic acid to zinc acetate is 3-3.6:
1.
4. The preparation method according to claim 1, characterized in that: In step (1), the heating and stirring are performed at a temperature of 50 to 60° C., a stirring rate of 500 to 1000 r / min, and a stirring time of 2 to 2.5 h.
5. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of ethanol to water in the ethanol-water solution is 9:
1.
6. The preparation method according to claim 1, characterized in that: In step (1), the precursor is heated to 450-550° C. at a heating rate of 2-10° C. / min for calcination, and the calcination holding time is 2-2.5 h.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In step (2), the mass-to-liquid ratio of activated carbon to acid / alkaline solution is 1:5-1:4 (g / mL); preferably, the alkaline solution is 1%-5% (w / w) KOH solution, and the acid solution is 4-5 mol / L nitric acid solution.
8. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of AC to ZnMn2O4 is 1:10 to 3:
10.
9. An AC / ZnMn2O4 photocatalytic regenerable adsorbent, characterized in that: The AC / ZnMn2O4 photocatalytic regenerable adsorbent is prepared by the preparation method according to any one of claims 1 to 8, and is composed of activated carbon AC and zinc manganate ZnMn2O4, wherein the mass ratio of AC to ZnMn2O4 is 1:10 to 3:
10.
10. Use of the AC / ZnMn2O4 photocatalytic regenerable adsorbent according to claim 9 in the cyclic adsorption of tannic acid.
Citation Information
Patent Citations
Particle electrode for photocatalytic three-dimensional electrode / electro-Fenton system and preparation method thereof
CN103739043A
Cellulose-based porous composite material and preparation method and purpose thereof
CN106179244A
Air purification photocatalyst
CN108722388A
Manganese tetroxide / zinc oxide composite material as well as preparation method and application thereof
CN111710535A
ZnMn2O4 hollow nano material as well as preparation method and application thereof
CN116924475A